Disability and discourse : analyzing inclusive conversation with people with intellectual disabilities - Williams, Val (Wiley-Blackwell, 2011)
For people with learning disabilities, effective communication presents a special set of challenges. By analyzing a series of real-life conversations and encounters between people with learning disabilities and those who work with them, this book provides illuminating insight into the ways people are treated in routine conversations